Social Protection of Persons with Disabilities in Nepal - Chaulagain, Rajendra; Pandey, Narayan (Journal of Social Protection, 2024)
This paper examines disability and social protection in Nepal highlighting the need for inclusion of persons with disabilities (PWDs) in the policies. Considering international evidence and that of the specific case of Nepal, the paper highlights problems that arise from the use of one size fits all approaches in catering for PWDs and suggests the formulation of specific strategies aimed at improving the welfare and participation of PWDs. Expansion of coverage of social security allowances, disability pensions, health services among other provisions, should also be accompanied by an emphasis on increased coverage and improved efficiency of existing schemes. There is need for coalition among the key players for policy change that promotes the rights, needs and welfare of PWDs. It is also important to undertake surveys that are devoid of vision in order to assess the effectiveness of social protection programmes intended for the disabled. Moreover, it is pertinent to bring practical policies and medical practices into effect aimed at ensuring the rights and social inclusion of the disabled in Nepal.